2014
DOI: 10.1007/s00429-014-0775-z
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal development of the molecular complex underlying astrocyte polarization

Abstract: Astrocytes are highly polarised cells with processes that ensheath microvessels, cover the brain surface, and abut synapses. The endfoot membrane domains facing microvessels and pia are enriched with aquaporin-4 water channels (AQP4) and other members of the dystrophin associated protein complex (DAPC). Several lines of evidence show that loss of astrocyte polarization, defined by the loss of proteins that are normally enriched in astrocyte endfeet, is a common denominator of several neurological diseases such… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
62
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 43 publications
4
62
2
Order By: Relevance
“…In accordance with recent studies (Lunde et al, 2014; Nwaobi et al, 2014), we found a continuous increase of Kir4.1 expression from being close to undetectable at E20 to being strongly expressed at adult stages (P60). These data are in agreement with studies suggesting that K ir channel expression correlates positively with cell differentiation (MacFarlane and Sontheimer 1997; Sontheimer et al, 1989; Barres et al, 1990; Olsen and Sontheimer, 2004) and with electrophysiological studies demonstrating that Kir4.1 channel activity increases during the first several postnatal weeks (Bordey and Sontheimer, 1997; Seifert et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…In accordance with recent studies (Lunde et al, 2014; Nwaobi et al, 2014), we found a continuous increase of Kir4.1 expression from being close to undetectable at E20 to being strongly expressed at adult stages (P60). These data are in agreement with studies suggesting that K ir channel expression correlates positively with cell differentiation (MacFarlane and Sontheimer 1997; Sontheimer et al, 1989; Barres et al, 1990; Olsen and Sontheimer, 2004) and with electrophysiological studies demonstrating that Kir4.1 channel activity increases during the first several postnatal weeks (Bordey and Sontheimer, 1997; Seifert et al, 2009).…”
Section: Discussionsupporting
confidence: 93%
“…Among the endfeetome, we found molecules already known to control cerebrovascular functions such as Cx43 (Gja1), which is implicated in BBB immune quiescence [8, 34], Agt, which plays a role in BBB integrity [35], or Aqp4, Kir4.1 (Kncj10), Hepacam and Mlc1, which are all involved in perivascular homeostasis [13, 30, 36]. Their presence strongly suggested that the endfeetome represents important astroglial functions for the regulation of the brain vascular physiology.…”
Section: Discussionmentioning
confidence: 99%
“…An obvious candidate is laminin. Laminin is a main constituent of the endothelial basal lamina and is among the first matrix molecules to appear at the endothelial‐endfoot interface (Lunde et al, ). However, in the present experiments, laminin did not induce any polarization on its own, nor did it enhance the polarizing effect of brain endothelial cells.…”
Section: Discussionmentioning
confidence: 99%